2020
DOI: 10.3390/ma13122793
|View full text |Cite
|
Sign up to set email alerts
|

Insights into In Vitro Wound Closure on Two Biopolyesters—Polylactide and Polyhydroxyoctanoate

Abstract: Two bio-based polymers have been compared in this study, namely: polylactide (PLA) and polyhydroxyoctanoate (PHO). Due to their properties such as biocompatibility, and biointegrity they are considered to be valuable materials for medical purposes, i.e., creating scaffolds or wound dressings. Presented biopolymers were investigated for their impact on cellular migration strategies of mouse embryonic fibroblasts (MEF) 3T3 cell line. Advanced microscopic techniques, including confocal microscopy and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…P(3HO) is already known for its numerous advantages in terms of biocompatibility and biodegradability. Due to its beneficial elasticity (Young's modulus 11.4-34 MPa) [4,14], endurance (friction coefficient 0.198-0.202), and low fragility (hardness 3.2-4.5 MPa) [1], it is being reviewed in terms of potential heart valve replacement, in wound-healing studies, and for joint endoprostheses [15][16][17]. Although in our previous works we ran a series of experiments describing the influence of P(3HO) on cell behavior, migration, morphology, and cytoskeleton, still there are some uncovered areas of interest on the specific substrate-cell interaction [1,4,18].…”
Section: P(3ho)mentioning
confidence: 99%
“…P(3HO) is already known for its numerous advantages in terms of biocompatibility and biodegradability. Due to its beneficial elasticity (Young's modulus 11.4-34 MPa) [4,14], endurance (friction coefficient 0.198-0.202), and low fragility (hardness 3.2-4.5 MPa) [1], it is being reviewed in terms of potential heart valve replacement, in wound-healing studies, and for joint endoprostheses [15][16][17]. Although in our previous works we ran a series of experiments describing the influence of P(3HO) on cell behavior, migration, morphology, and cytoskeleton, still there are some uncovered areas of interest on the specific substrate-cell interaction [1,4,18].…”
Section: P(3ho)mentioning
confidence: 99%
“…The authors reported that the surface properties of P(3HO), i.e., the coefficient of friction, combined with lower brittleness of the materials compared to other biodegradable and biocompatible polyesters such as poly(lactic acid) (PLA) and P(3HB), may indicate potential applications of P(3HO) in the construction of medical implants, joint endoprostheses. It should be underlined that the above materials are not only subjected to significant loads (hip joint, knee joint), but also high friction forces due to their movement in contact with bones or cartilage [ 30 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observations were made with an air 10× objective. For DAPI stain excitement a wave with length of 405 nm was applied [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all these reports bring up other ideas in the final establishment of the processes standing behind the nucleus mechanics, we decided to check the influence of the microenvironment on the presence of the nuclei invaginations and blebs. To explore this further, we stained vimentin, microtubules, actin, and nucleus, and used confocal microscopy imaging for mouse embryonic fibroblast 3T3 cells, cultured on glass, and two substrates of high potential use in medicine: polylactide (PLA) [ 25 , 26 ] and polyhydroxyoctanoate (PHO)—a polymer of biological origin [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%